Urban changes in Braga in late antiquity: the area of the Roman Theater - Martins, Manuela (2015)
This work intends to value the urban and constructive changes that occurred in the abandoned spaces of the Roman theater of Bracara Augusta, as well as in its surroundings as a contribution to establish the evolution of the city of Braga in Late Antiquity. The theater was located to the west of the forum and was built at the beginning of the second century together with an attached public thermal building. Its construction is associated with an important urban renewal that reshaped the western sector of the city in a moment of great economic prosperity during which the city reached its maximum extension. Following its abandonment in the fourth century part of the building was dismounted and it has been punctually reused in the V-VI centuries. Meanwhile, the excavations carried out in the surrounding areas of the theater facade revealed remains of new constructions with the same chronology, that occasionally reused its wall. The nature of those identified structures and its chronology show the importance of this area of the city to analyze the urban evolution of Braga during the Early Middle Ages.